Inflation, inflation uncertainty and growth in the Iranian economy: an application of BGARCH-M model with BEKK approach - Heidari, Hassan; Katircioglu, Salih Turan; Bashiri, Sahar (Journal of Business Economics and Management, 2013)
This paper investigates the relationship between inflation, economic growth and their respective uncertainties in Iran for the period of 1988–2008 by using quarterly data. We employ a Bivariate Generalized Autoregressive Conditional Heteroskedasticity-in-Mean (BGARCH-M) model to examine in a unified empirical framework all the possible interactions between inflation uncertainty and growth in Iran. The model is simultaneously estimated by using the maximum log-likelihood method with the BEKK approach. The main findings of the present study are: (1) Inflation causes inflation uncertainty, supporting the Friedman-Ball hypothesis. (2) Inflation uncertainty affects the level of economic growth, supporting the Friedman (1977) hypothesis. (3) Growth uncertainty does not affect the level of economic growth, supporting the Friedman (1968) hypothesis. (4) And finally our empirical evidence shows that growth uncertainty affects the level of inflation, supporting the Deveraux (1989) hypothesis.